The thermal-flow performance of water-Al2O3 nanofluid flow in an elliptical duct heat exchanger equipped with two rotating twisted tapes - Hassan Wathiq Ayoob; Ihab Omar; Wed khalid Ghanim; Mohammad N. Fares; Mohammad Ali Fazilati; Soheil Salahshour; Sh Esmaeili (Case Studies in Chemical and Environmental Engineering)
Background: The thermal-flow performance of nanofluid (NF) flow in an elliptical duct heat exchanger fitted and turbulated with two rotating tapes is investigated. The issues concerning rotating twisted tapes inside the oval tubes using NF as the working fluid simulated with two-phase modeling have received less attention in previous studies. Methods: Considering the importance of employing the heat transfer improving methods in tubular heat exchangers, the passive and ative heat transfer improving methods examined here. As a novel study case, the rotated tapes beside the water-Al2O3 NF of was used; and sensitivity analysis was performed to reveal the effect of the volume fraction of nanoparticles (ϕ), tapes rotational speed and Re number on the Nu number, pumping power and figure of merit (FOM). The heat flux of 5000 Wm−2 was applied to the wall surface, and the two-phase mixture method was employed for the simulation. The heat exchanger performance is studied in cases of fixed and rotating twisted tapes with three different rotational speeds. The results show that increasing the Re number, ϕ and the rotation speed of the blades would increase the Nu number and pumping power in all cases. The increase in ϕ improves the Nu number by 6.1 %–19.4 % and the pumping power by 59.2–280 %. The Nu number change by increasing ϕ is lower at low Re numbers and becomes higher at high Re numbers. The effect of ϕ increment on heat transfer is increasing but took place with a higher inclination rate in rotating tapes rather than stationary tapes and plain tube cases. In the cases of rotated twisted tape mode, the value of FOM is always greater than one and is below 0.9 for stationary mode. Significant findings: The highest value of FOM is 1.57, which is for the highest rotational speeds, the lowest Re number, and ϕ = 1 %. Increasing the Re number reduces the FOM while increasing ϕ improves it. Practical significance and potential area of application: The increasing need for efficient heat transfer in heat exchanger devices necessitated the application of heat transfer augmentation techniques. The effects of twisted tapes, their rotation, and the application of NFs in heat exchangers as the active and passive heat transfer increment methods are studied numerically.